2019
DOI: 10.1021/acs.inorgchem.8b02860
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Cage/Guest Assemblies: Photoinduced Electron Transfer between a Coordination Cage Containing Osmium(II) Luminophores, and Electron-Deficient Bound Guests in the Central Cavity

Abstract: A heterometallic octanuclear coordination cage [Os4Zn4(Lnap)12]­X16 (denoted Os•Zn; X = perchlorate or chloride) has been prepared (Lnap is a bis-bidentate bridging ligand containing two pyrazolyl–pyridine chelating units separated by a 1,5-naphthalenediyl spacer group). The {Os­(NN)3}2+ units located at four of the eight vertices of the cube have a long-lived, phosphorescent 3MLCT excited state which is a stronger electron donor than [Ru­(bipy)3]2+. The chloride form of Os•Zn is water-soluble and binds in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Thus the carbonyl group of a range of bulky aliphatic ketone guests is always anchored in this way, as is the carboxylate terminus of adamantane‐1‐carboxylate . When a single guest contains two H‐bond accepting functional groups with the correct separation it can span the cavity diagonally and interact with both H‐bond donor sites simultaneously, as we saw recently using 1,2,4,5‐tetracyanobenzene as a guest …”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Thus the carbonyl group of a range of bulky aliphatic ketone guests is always anchored in this way, as is the carboxylate terminus of adamantane‐1‐carboxylate . When a single guest contains two H‐bond accepting functional groups with the correct separation it can span the cavity diagonally and interact with both H‐bond donor sites simultaneously, as we saw recently using 1,2,4,5‐tetracyanobenzene as a guest …”
Section: Resultsmentioning
confidence: 89%
“…In some of our earlier studies of guest binding, NMR titrations of the host cage with guests in solution sometimes showed that free and bound guest are in fast exchange on the NMR timescale: this results in a steady shift for the signal being observed as the titration proceeds, and the resulting binding curves could normally be satisfactorily fit to a 1:1 model . The sole exception to this was with the small guest DMMP (mentioned earlier), for which clear evidence of a H⋅G 2 complex was obtained from the NMR titration.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations